ex 4) Fie expresia E(x):
![Ex 4 Fie Expresia Ex class=](https://ro-static.z-dn.net/files/dde/49cddfbcf5d2ced2a6f2a3062447efcb.jpg)
Salut!:)
a) E(x) = ( x + 5 )² + 2( x + 5 )( x - 4 ) + ( x - 4 )² = ( x + 5 + x - 4 )² = ( 2x + 1 )²
b)
[tex] \sqrt{(2x + 1)^{2} } = |2x + 1| [/tex]
[tex] = > - 3 \leqslant 2x + 1 \leqslant 3 \: | - 1 \\ - 4 \leqslant 2x \leqslant 2 \: | \div 2 \\ - 2 \leqslant x \leqslant 1[/tex]
=> x = [ - 2, 1 ] => A = [ - 2, 1 ]
A n Z = { - 2, - 1, 0, 1 }
- 2 × ( - 1 ) × 0 × 1 = 0